1995
DOI: 10.4326/jjcvs.24.190
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for Starr-Edwards Ball Valve Insufficiency 21 Years after Replacement.

Abstract: A 51-year-old woman, who had undergone mitral valve replacement with the Starr-Edwards ball valve 21 years ago, was hospitalized with cardiac failure. Preoperative cineangiograms showed delay of the ball movement during the early diastolic phase. Re-replacement of the mitral prosthetic valve with a CarboMedics prosthetic valve and tricuspid annuloplasty was successfully performed. The postoperative period after the initial implantation of the Starr-Edwards ball valve is the longest among patients reported in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…6 However, other authors have reported significant chronic hemolysis, thromboembolism, variance of the silastic ball and tissue ingrowth of the paravalvular area. 2,3 In the present case, although the preoperative echocardiogram showed that the aortic S-E valve prosthesis that had been implanted 28 years previously was functioning normally, prophylactic replacement was perfomed at the same time as the mitral valve replacement, coronary artery bypass grafting and TAP. Grunkemeier and Starr suggested that prophylactic reoperation for S-E bare strut ball valves is not indicated in the current subset, 2 and Lund et al reported that S-E aortic ball valves, including the currently available silastic ball valves, are durable for the remaining life span of the patients who can expect near normal ageand sex-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, other authors have reported significant chronic hemolysis, thromboembolism, variance of the silastic ball and tissue ingrowth of the paravalvular area. 2,3 In the present case, although the preoperative echocardiogram showed that the aortic S-E valve prosthesis that had been implanted 28 years previously was functioning normally, prophylactic replacement was perfomed at the same time as the mitral valve replacement, coronary artery bypass grafting and TAP. Grunkemeier and Starr suggested that prophylactic reoperation for S-E bare strut ball valves is not indicated in the current subset, 2 and Lund et al reported that S-E aortic ball valves, including the currently available silastic ball valves, are durable for the remaining life span of the patients who can expect near normal ageand sex-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…McGoon et al reported that these prostheses implants were durable over a prolonged follow-up period, while thromboembolism remained a persistent problem [5]. Different kind of complications have been reported including haemolytic anaemia, valve dysfunction caused by granulomatous hyperplasia, degeneration or lipid infiltration of the silicon ball and wearing out of the cloth cover [6,7].…”
Section: Introductionmentioning
confidence: 99%